The Secondary Market for Life Insurance in the U.K., Germany, and the U.S.: Comparison and Overview - Gatzert, Nadine (Risk Management and Insurance Review, 2010)
In this article, we identify key characteristics and implications of the secondary market for life insurance. We examine the oldest secondary market, which is the market in the United Kingdom, the relatively young market in Germany, and the controversial U.S. market. We summarize the available data to describe the current market situation and market potential, which strongly depend on developments in the primary markets and capital markets, as well as on regulatory and legal aspects. Next, we discuss benefits and risks associated with a secondary market, which depend on each market's unique features. The three markets considered in this article are fundamentally different, and the comparative assessment is intended to offer insight into their functioning and key factors.
WiSo-Import:2015-03-26:951
Keywords: Forschungsbericht 2010; Kohäsion